2009
DOI: 10.1177/1087054708325976
|View full text |Cite
|
Sign up to set email alerts
|

ADHD in the Arab World

Abstract: There is an important need for research on ADHD in the Arab World, not only to assess the national prevalence in children and adolescents, but also to look at the differential burden and treatment of this disorder, which has high levels of mental comorbidities and high impact across the life span.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 36 publications
3
17
2
Order By: Relevance
“…The prevalence of ADHD in this study is 10.2% and is relatively high compared to prevalence estimates reported in other parts of the Arab world [19] and in an earlier Lebanese study [11] which found a prevalence of 3.2% among school-aged children using a teacher rating scale. Our high prevalence could be explained by a difference in methodology as our study used a structured diagnostic tool to interview both adolescents and their parents in order to make a diagnosis based on DSM-IV criteria, whereas most other regional studies were conducted in school samples, surveyed pre-adolescent children, and relied on self-questionnaires or teachers’ rating scales [19, 20].…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The prevalence of ADHD in this study is 10.2% and is relatively high compared to prevalence estimates reported in other parts of the Arab world [19] and in an earlier Lebanese study [11] which found a prevalence of 3.2% among school-aged children using a teacher rating scale. Our high prevalence could be explained by a difference in methodology as our study used a structured diagnostic tool to interview both adolescents and their parents in order to make a diagnosis based on DSM-IV criteria, whereas most other regional studies were conducted in school samples, surveyed pre-adolescent children, and relied on self-questionnaires or teachers’ rating scales [19, 20].…”
Section: Discussioncontrasting
confidence: 49%
“…Our high prevalence could be explained by a difference in methodology as our study used a structured diagnostic tool to interview both adolescents and their parents in order to make a diagnosis based on DSM-IV criteria, whereas most other regional studies were conducted in school samples, surveyed pre-adolescent children, and relied on self-questionnaires or teachers’ rating scales [19, 20]. Furthermore, although our sample was socioeconomically diverse, our sampling area was uniformly urban, and studies conducted in urban environments have been associated with increased parental reporting of ADHD [21].…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing number of studies regarding ADHD in children and adolescents in Arab countries, there are still a small number of studies conducted in adult populations with most of them were limited by a small sample size. 43 One of the studies addressing the issue of adult ADHD was carried out in Lebanon, 37 but only as part of an international World Health Organization study, in which the prevalence of adult ADHD was estimated at 1.8%. 44 The authors explained that the low rate of adult ADHD reported in this study was attributed to the use of a structural interview (associated with low rates), and respondents under-reporting their symptoms in interviews due to the stigma of mental illnesses in the Arab world.…”
Section: Discussionmentioning
confidence: 99%
“…In the Arab region only one systematic review was completed in 2009. 15 However, with increased interest in research on ADHD, several new studies have been conducted in the Arab world. This systematic review provides an update on the current state of knowledge with respect to ADHD literature in the Arab world.…”
mentioning
confidence: 99%
“…Moreover, in two studies conducted in Saudi Arabia to elaborate prevalence of ADHD among primary school students revealed that the prevalence ranged between 12.6% in Riyadh, and 16.4% in Dammam (Bener, Qahtani, & Abdelaal, 2006). Farah et al (2008) found children with ADHD rates in Arab populations were similar to those in other cultures, According to the Arab; results in all Arab studies in (i.e., Kingdom of Saudi Arabia, United Arab, Lebanon, Qatar) reporting on gender differences showed that the prevalence rate of ADHD was higher in males than in females with ratios varying from 2:1 to 3:1, which is compatible with the international literature on ADHD in both epidemiological and clinical samples.…”
mentioning
confidence: 99%